X-Ray Fluorescence Spectrometry Data for IODP Hole 369-U1513D - Maria Luisa G Tejada; Hans-Jürgen Brumsack; Bernhard Schnetger (PANGAEA, 2020)
Bulk rock composition analysis was conducted by X-Ray Fluorescence spectrometry (WD-XRF) using AXIOS Plus (Panalytical) at University of Oldenburg on shipboard residual sample powders analyzed by ICP-AES [Huber et al., 2019]. Borate glass beads were prepared from the sample powder using di-lithium tetraborate as a flux (700 mg sample, 4.2 g flux). Calibration of the XRF instrument is based on 52 international reference samples and in-house standards. Precision was determined from the pooled standard deviation of several duplicates and is better than 3% for major elements and better than 5% for trace elements when concentration levels are above the limit of quantitation. Accuracy was checked by analyzing international and in-house reference samples that are not included in the calibration and was better than 7% for all elements above the limit of quantitation. Results between XRF and ICP-AES analysis are generally in excellent agreement, except for elements affected by incomplete dissolution in borate digestion, especially Cr, and low-abundance elements like Rb and Nb that were not measured well by ICP-AES.